A GENDER AND MARITAL STATUS ANALYSIS OF HOUSEHOLD INCOME IN A LOW-INCOME TOWNSHIP - DUNGA, Steven Henry (Studia Universitatis Babeș-Bolyai Oeconomica, 2017)
https://doi.org/10.1515/subboec-2017-0002 The analysis of income at household level is highly important for understanding the poverty and for supporting the efforts to deal with poverty. Poverty measures can be calculated from a multitude of approaches. A common approach is to use household income and draw a minimum level of income required for a household to be considered above or below poverty. This paper looked at income at household level from a gender perspective and a marital status perspective in order to draw conclusions of the nature of household’s characteristics that are associated with higher or lower income as a proxy for poverty. Based on data collected in a low income township in South Africa, the regression analysis was applied to investigate the differences between different marital statuses and gender and how they are associated with different levels of income. The regression results reveal that female headed households have, on average, lower incomes compared to male headed households, and also, that married heads of households have higher incomes compared to the single, divorced, and widowed. The widowed had the lowest average income. JEL classification: I32